Aulas noturnas e ensino prisional: iniciativas de uma educação popular na Parahyba do Norte (1870-1889) - Costa, Suênya do Nascimento (2022)
This thesis aims to identify evening classes as a segment of popular education that sought to spread education to the people in the Northern Parahyba Province. The time frame begins in 1870, due to the publication of Law No. 400 of December 19th, which created the evening classes in the province of Paraiba, and, as a final milestone, in the year 1889, marking the end of the empire in Brazil, the changes in political regime and, consequently, in educational legislation. This time period was thought of for the time cut, because the evening schools created during the aforementioned decade were perceived as an alternative for the schooling of the free, poor, liberated and naive worker in the province of Paraiba. From this, other objectives, in a more specific way, sought to identify the different concepts attributed to categories such as people, citizens and popular education in the processes of propagation of schooling; to understand how the discourses of the authorities sought to legitimize the creation and organization of evening classes linked to a discourse on labor and training of the "useful citizen" and to analyze how the classes in the jails composed, together with the evening classes, a concept of popular education that served as an alternative by the authorities in controlling certain groups of the population. The thesis argument is that evening classes served as a segment that would provide an education considered popular according to the concepts of the period, linking education and labor to form subjects considered useful for society. The theoretical and methodological contributions are developed in a dialogue between the Linguistic Contextualism defended by the English historian Quentin Skinner (1999, 2005), for what the subjects intended to say, as well as the way in which they wished their ideas to be taken; the Conceptual History advocated by the German historian Reinhart Koselleck (1992, 2006), in order to understand the semantic contents coming from political and historical concepts of the period; and the Social History of Labor, thinking about the labor relations of the 19th century historical context, mainly with the contributions of Sidney Chalhoub (1986, 1990) and Marcelo Mac Cord (2009, 2010, 2012). The analyzed sources cover newspapers, reports, regulations, laws, decrees, among other documents that contribute to the historiography of education by focusing on the educational discourse in its contexts of production, interpreting on the basis of traces present in the analyzed sources on the schooling of a specific portion of the population. Thus, we point to the debate around evening schooling, popular education and labor, in addition to the political character of language, which is now understood as an instrument used in the attempt to legitimize projects and ideas, amid the debates and clashes held around certain themes of the late nineteenth century.